Evaluation of hematuria and proteinuria positivity in relation to ageing in 6,651 apparently healthy men and women - Shimabukuro, Tomoyuki (Hinyokika kiyo. Acta urologica Japonica, 2007)
We examined the positivity of hematuria and proteinuria in relation to ageing in 6,651 apparently healthy persons (2,556 women and 4,095 men) who underwent multiphasic health screening in our Medical Checkup Center. Commercially available dipsticks were used. The time from urine collection to dipstick analysis was within 60 minutes. The mean age of women was 48.2 years (range 10 to 82) and that of men was 49.9 years (range 7 to 89). Approximately 30.1, 1.5, and 0.7% of the women had hematuria, proteinuria, and hematoproteinuria, respectively; and 11.4, 4.0, 1.5% of the men had the corresponding urine abnormalities, respectively. Hematuria was 2.6 times more common in women than in men, and proteinuria was 2.7 times more common in men than in women. The positivity of hematuria increased linearly with age in women (Rs = 0.943, P = 0.0350). On the other hand, the positivity of proteinuria or hematoproteinuria was not correlated with age (P = 0.8386 and P = 0.0639, respectively). In men, the positivity of hematuria or hematoproteinuria was not correlated with age (P = 0.0845 and P = 0.0845, respectively). However, the positivity of proteinuria in those more than 30-year age group increased linearly with age (Rs = 1.000, P = 0.0455). The true meaning of such gender- and/or age-related differences in urinary abnormalities remains to be determined